Aplikasi Mobile Health untuk Mendeteksi Dini Gelombang Kejang pada Anak dengan Gangguan Epilepsi - Betti Arisanti Saragih; Sigit Mulyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aimed to detect seizures early on the mobile health application in children with epilepsy. The research method used was the literature review database at the University of Indonesia, namely Science Direct, ProQuest, Scopus, EBSCOhost, and Google Scholar (2018-2022. The results of this study show that a review literature search obtained from seven journals showed that the mobile health application is used to detect seizure waves in children. A lot of review literature on mobile health can detect seizure waves early so that parents or caregivers can prepare themselves before seizures appear in children using mobile health. The application can also improve patient medication adherence, assist in documenting seizures, and increase knowledge about epilepsy for children, parents, or caregivers. In conclusion, mobile health applications benefit children with epilepsy in self-management. Keywords: Epilepsy, EEG, Mobile Health Application